On Juneteenth - Gordon-Reed, Annette (2021)
""It is staggering that there is no date commemorating the end of slavery in the United States." -Annette Gordon-Reed. The essential, sweeping story of Juneteenth's integral importance to American history, as told by a Pulitzer Prize-winning historian and Texas native. Interweaving American history, dramatic family chronicle, and searing episodes of memoir, Annette Gordon-Reed, the descendant of enslaved people brought to Texas in the 1850s, recounts the origins of Juneteenth and explores the legacies of the holiday that remain with us. From the earliest presence of black people in Texas-in the 1500s, well before enslaved Africans arrived in Jamestown-to the day in Galveston on June 19, 1865, when General Gordon Granger announced the end of slavery, Gordon-Reed's insightful and inspiring essays present the saga of a "frontier" peopled by Native Americans, Anglos, Tejanos, and Blacks that became a slaveholder's republic. Reworking the "Alamo" framework, Gordon-Reed shows that the slave-and race-based economy not only defined this fractious era of Texas independence, but precipitated the Mexican-American War and the resulting Civil War. A commemoration of Juneteenth and the fraught legacies of slavery that still persist, On Juneteenth is stark reminder that the fight for equality is ongoing"--
"This, then, is Texas" -- A Texas town -- Origin stories : Africans in Texas -- People of the past and the present -- Remember the Alamo -- On Juneteenth -- Coda
Includes bibliographical references
Keywords: Juneteenth; Slaves -- Emancipation -- Texas; African Americans -- Texas -- Galveston -- History; African Americans -- Anniversaries, etc; African Americans -- Social life and customs; Slaves -- Emancipation -- United States; History; History; History